Antioxidant Potential and Phytochemical Screening of Extracts from Senegalia nigrescens-A Traditional Swazi Medicinal Plant - Pillai, Manoharan Karuppiah; Siwela, Samkelisiwe Nokuphila (Fine Chemical Engineering, 2024)
Senegalia nigrescens has been used in traditional Swazi medicine. S. nigrescens is used in the treatment of wounds, toothache, diabetes, dysentery, snake bites, convulsions and skin diseases. In this study, we aimed to evaluate the antioxidant potential, determine the half-minimal inhibition concentration (IC50) values and analyze phytochemical constituents of various solvent extracts obtained from the leaves and stem-bark of S. nigrescens. The maceration technique together with the hot solvent extraction approach was used for the obtainment of various solvent extracts. 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging potential, IC50 values and phytochemical analysis were performed as per established procedures. The radical scavenging potential of extracts from leaves and stem-bark of S. nigrescens and positive control (ascorbic acid) were found to be in the ranges of 7.55 ± 0.004 ~ 62.19 ± 0.004%, 9.04 ± 0.003 ~ 63.24 ± 0.006% and 50.98 ± 0.002 ~ 71.0 ± 0.007%, respectively at a concentration range of 200 ~ 3,000 μg/mL. The methanol extracts from the leaves, stem-bark and positive control exhibited IC50 values of 921.69, 735.74 and < 200 μg/mL, respectively. Several classes of phytochemicals were identified in these extracts which include alkaloids, steroids, terpenoids, flavonoids, phenolics and tannins. We concluded that S. nigrescens showed a weak to moderate DPPH radical scavenging potential and possessed various classes of phytochemicals.